Pengaruh Financial Distress, Reputasi KAP, Size dan Audit Delay Terhadap Auditor Switching - Hapsa Kuzaemah; Imam Hadiwibowo; Mohammad Taufik Azis (Jurnal Proaksi, 2023)
Auditor independence is one of the main things for auditors, to maintain the level of auditor independence, the government issued regulations related to auditor rotation. The purpose of this study was to examine the effect of financial distress, KAP reputation, company size and audit delay on auditor switching. This study uses a sample of manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The sample used is purposive sampling. There are 75 companies that meet the sample criteria. Testing the hypothesis in this study using logistic regression analysis. Then the data that has been collected and analyzed is processed using the IBM Statistical Package for Social Sciences (SPSS) version 22 program. The test results show that financial distress has an effect on auditor switching, KAP reputation and company size have no effect on auditor switching, while audit delay has an effect on auditor switching. Taken together financial distress, KAP reputation, company size and audit delay on auditor switching.